The Effects Of Photographic Presentation Modes On Semiotic Understanding Of Land Art Among Iranian Art Students - Najafi, Farzaneh (2014)
Land art consists of sculptures, carvings, and performances located at specific natural surroundings to deliver messages of love and concern for the environment. As they are ephemeral or located in inaccessible places they are documented for reference in the form of photographs taken by the artists or by people interested in the works. Seni bumi terdiri dari arca, ukiran, dan persembahan yang dibuat di lokasi semulajadi tertentu untuk menyampaikan mesej cinta dan keperhatinan terhadap alam sekitar. Oleh kerana hasilan seni ini adalah bersifat sementara atau ditinggalkan di lokasi-lokasi yang sukar dilawati maka dokumentasi hasilan karya ini dibuat melalui gambar-gambar foto yang diambil oleh artis-artis berkenaan atau penggemar-penggemar seni tersebut.